Facile synthesis of D-xylulose-5-phosphate and L-xylulose-5-phosphate by xylulokinase-catalyzed phosphorylation. Issue 1 (2nd January 2020) - Hardt, Norman; Kind, Stefanie; Schoenenberger, Bernhard; Eggert, Thorsten; Obkircher, Markus; Wohlgemuth, Roland
Abstract: The enantiomeric metabolites D-xylulose-5-phosphate and L-xylulose-5-phosphate are highly relevant in numerous important pathways from microbial to human metabolism. As these phosphorylated chiral metabolites are required for the analysis of enzyme activities, pathways and biological functions in health and disease, efficient and straightforward methodologies for their synthesis are needed. Biocatalytic phosphorylations of their corresponding monosaccharides offer single step synthetic routes. Therefore, D- and L-xylulokinases have been selected, the XKS1 gene from Saccharomyces cerevisiae and the lyx gene from Escherichia coli have been synthesized and cloned into an appropriate expression vector to allow for the production of the enzymes in E. coli . The expression has led to highly active xylulokinases in the soluble fractions, which could be directly used for the biocatalytic phosphorylation of D- and L-xylulose, using the phosphoenolpyruvate(PEP)/pyruvatekinase(PK)-system for the regeneration of the ATP cofactor. The time course of the phosphorylation reactions has been monitored by 31 P-NMR and 1 H-NMR spectroscopy and the monosaccharide substrates could be phosphorylated with nearly 100% conversion. After standard workup, both the D-xylulose-5-phosphate and the L-xylulose-5-phosphate have been obtained in high yield and purity. Abstract :